White Quest Synergy Sdn Bhd / Muhammad Aiman Mohamad Rosli - Mohamad Rosli, Muhammad Aiman (Faculty Of Chemical Engineering, 2021)
UiTM has always strived to develop well-rounded students with outstanding academic accomplishments, improved communication skills, and leadership abilities that will aid them in their future endeavours. The students' enrolment in this industrial training has provided them with the chance to obtain real-world job experience and gain a better understanding of the industries. In a nutshell, there are many things I've learnt throughout my internship with White Quest Synergy during the last four months. Many unforeseen events occurred that I had to deal with in order to earn my diploma; it is a bitter-sweet memory for me. Working in the real world is not simple, and even a minor blunder may quickly transform a situation into a disaster. This training taught me to think in a variety of ways and to think beyond the box. It was not easy for me, but I am thankful for the chance to experience both industrial and work-from-home job styles; it was an excellent learning experience that will help me prepare for the future. If I had another chance for industrial training, I would choose 'hands-on' industrial training since it exposes me to the realities of chemical engineering. Working with White Quest Synergy, on the other hand, was an incredible experience for me